On the early studies recognizing the role of sulphuric acid in atmospheric haze and new particle formation. Issue 1 (1st January 2018) - Malila, Jussi
Abstract: Atmospheric aerosols have been a subject to scientific interest at least since the Age of Enlightenment, including theories concerning the origins of atmospheric haze and dust. Early studies associated haze with geological sources – earthquakes and volcanism – which were believed to be related to the chemistry of sulphuric compounds. Thus, sulphuric acid became the strongest candidate to explain atmospheric new particle formation. The idea was carried over when the first quantitative studies of condensation nuclei and atmospheric chemistry took place during the later part of the 19th century. Laboratory and field measurements by von Helmholtz, Aitken, Kiessling, and Barus, among others, a century ago led to the conclusion that widespread new particle formation occurs in the atmosphere and is caused by sulphuric acid together with water and ammonia – a viewpoint, which has been rediscovered and expanded during the past 25 years.